Issues of Ensuring the Quality of Education as a Common Good in the World of Digital Communications - Tuychiyevna, Razikova Lola (International Journal on Orange Technologies, 2023)
The article discusses the distinctive features of the adaptation of the education sector to the processes of introducing digital technologies, as well as the challenges facing educational systems around the world. The author examines the activities of UNESCO in terms of the adoption of generally significant documents aimed at progress in ensuring the availability and quality of education in the information age. In conclusion, conclusions and recommendations are given aimed at the effective interaction of the factors of educational relations.